Ultraviolet curing water-based insulating paint and preparation method thereof

By using ultraviolet cured water-based insulating coatings in the battery coating, combining polyamide and amino functionalized silica, to form a grid-like structure and thickening effect, the problem of high surface roughness of traditional coatings is solved, and a battery coating with high flatness and high wear resistance is achieved, which improves the safety and durability of the battery.

CN119639311APending Publication Date: 2025-03-18SHENZHEN LIJIAN BONA TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510024931.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional battery packaging methods such as blue film and powder spraying have problems such as poor uniformity and low yield. In the process of improving adhesion and heat resistance, water-based insulating coatings can easily lead to an increase in the surface roughness of the coating, affecting the safety of the battery.

Method used

UV curing aqueous insulating coating is used, by adding aqueous epoxy resin, nonionic emulsifier, diluent, second filler and polyacrylic leveling agent to component A, and adding curing agent, first filler, gas silicon and water to component B, combining polyamide as the curing agent, amino functionalized silica as the first filler, and silicon oil as the second filler to form a grid-like structure and thickening effect, improving the flatness and wear resistance of the coating.

Benefits of technology

It achieves high flatness and wear resistance of the battery coating, reduces the unevenness of the coating surface, and improves the safety and durability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 1F4ESHNM5HJIE5TJ6OPN453W0ED6XVPZMYAURDGA
    Figure 1F4ESHNM5HJIE5TJ6OPN453W0ED6XVPZMYAURDGA
  • Figure AORPVSIZUTGCJVAH4L7GBOKTXRCZIZ2TQVRTD5IT
    Figure AORPVSIZUTGCJVAH4L7GBOKTXRCZIZ2TQVRTD5IT
  • Figure DZS3LIYMN4EIF2FFCBKBHU49HO6KJ6ANRYXD815I
    Figure DZS3LIYMN4EIF2FFCBKBHU49HO6KJ6ANRYXD815I
Patent Text Reader

Abstract

The invention relates to the field of insulating paint, in particular to a preparation method of ultraviolet curing water-based insulating paint. According to the invention, the amidated silicon dioxide is adopted as the filler, and the silicone oil, the gaseous silicon and the polyacrylic acid flatting agent are added, so that a smooth and wear-resistant surface is formed in a double-component co-curing system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of insulating coatings, and in particular to a method for preparing a UV-curable water-based insulating coating. Background Art

[0002] In recent years, with the development of new energy vehicle industry, the battery industry has also flourished. The battery surface needs to be packaged with insulating materials. Traditional packaging methods are generally blue film or powder spraying. The above two methods generally have poor uniformity and low yield. Therefore, at present, all companies are looking for a new method to replace the traditional packaging method.

[0003] There is currently a wide range of research on the use of water-based insulating coatings for battery packaging. It is cost-effective, has good uniformity and stability, and has a significantly higher yield rate than blue film packaging and powder coating, so it has attracted the attention of major manufacturers. Among many water-based coatings, materials based on epoxy resins have good adhesion properties, and can introduce more aromatic rings inside to improve the heat resistance of the system. It is also the first echelon in current battery coatings.

[0004] In order to improve the wear resistance, rigidity and insulation performance of the epoxy resin layer, a portion of inorganic fillers such as hydroxyapatite and aluminum nitride are usually added to the system. However, in thinner coatings, the above materials sometimes lead to increased surface roughness of the coating. In addition, in order to improve the adhesion and strength of epoxy resins, increasing the high functionality of epoxy resins is also a commonly used technical means. The poor fluidity caused by high functionality will also lead to increased viscosity of the system and increased surface roughness after curing. When the roughness increases, the coating on the surface of the battery is more susceptible to wear, which in turn creates safety hazards. Summary of the invention

[0005] The purpose of the present application is to provide an epoxy resin coating for battery surface coating, which has good wear resistance and surface smoothness, thereby improving the safety of the battery.

[0006] First, the present application provides a UV-curable water-based insulating coating, comprising component A and component B, wherein component A comprises the following components in parts by mass: Water-based epoxy resin 100 parts Nonionic emulsifier 5-20 parts 5-10 parts of diluent 5-8 parts of the second filler Polyacrylic acid leveling agent 0.1~1 part 2-4 parts silicone oil 0-5 parts water Component B includes the following components in parts by mass: Curing agent 8-15 parts 3-5 parts of the first filler 0.5~2 parts of gas silicon 5-10 parts water The curing agent is a polyamide compound, and the amine value of the polyamide compound is 5000 to 10000 (mgKOH / g); The first filler is amino-functionalized silica; The viscosity of the silicone oil is 1000-5000 cs.

[0007] In the above scheme, polyamide is first selected as the curing agent in the system, and at the same time, some amino groups are introduced into the surface of the first filler, thereby providing a more uniform curing structure. In this system, the amino groups on the surface of the first filler can partially couple the epoxy resin to the surface of the first filler. In this process, the first filler can be better cured on the inner wall of the system, thereby making it less likely for the system as a whole to have an uneven structure on the surface. At the same time, the multi-distance coupling performance of the first filler is utilized to form a grid-like structure in the system, thereby reducing the collapse and shrinkage of the surface during the curing process, and further improving the flatness of the system surface.

[0008] On the basis of the above, the fluidity of the epoxy resin system is further adjusted through multiple components. The addition of polyacrylic acid leveling agent can improve the flatness of the surface after coating, so that the epoxy resin can be better dispersed in the system, and can provide fluidity before curing, so that the filler components are evenly distributed in various areas. The gas silica can play a certain degree of thickening role in the system, making the coating less likely to flow freely. At the same time, it also provides a certain filling effect, so that the small space caused by shrinkage inside the coating can be filled with gas silica. At the same time, the larger specific surface area of ​​gas silica can also promote the formation of curing. The above effects can make the system smoother.

[0009] Furthermore, silicone oil is added to the above system, which provides uniform viscosity and fluidity, as well as good heat resistance. Overall, the surface is smoother and the wear resistance is better after adding silicone oil.

[0010] Preferably, the average particle size of the amino-functionalized silica is 1 to 10 μm. The above silica has good strength and has little effect on the fluidity of the system, and can provide better flatness and reaction performance.

[0011] Preferably, the amino-functionalized silica is silica-grafted polycaprolactam. More preferably, the mass ratio of the polycaprolactam to the silica is 1 to 5:1.

[0012] In the above scheme, the polycaprolactam molecular chain is used to make the reaction performance of the surface of the silica particles better, which is more conducive to its participation in the curing process of the epoxy resin. At the same time, the flexibility of the molecular chain can reduce the impact of the first filler on the fluidity in the system and reduce the agglomeration of the first filler and the second filler. Overall, compared with the method of directly introducing amino groups on the surface of the system using a silane coupling agent, this method can better improve the flatness of the system.

[0013] The number average molecular weight of the curing agent is preferably 3000 to 5000, and the overall curing performance and curing effect are good, thereby providing good mechanical properties, curing properties and surface smoothness.

[0014] Preferably, the thermal conductivity of the second filler is not less than 25 W / m·K, and the average particle size of the second filler is not greater than 1 μm. Further preferably, the second filler is nano-alumina or nano-silicon nitride, and the average particle size is 50-200 nm.

[0015] In the above scheme, the second filler is used to improve the thermal conductivity of the system, and aluminum oxide is used, which has good mechanical properties, significantly enhanced surface wear resistance, and improved peel strength. In addition, the aluminum oxide is selected to have a smaller particle size, which also helps to further improve the flatness.

[0016] Preferably, the waterborne epoxy resin contains 5-10% by mass of aliphatic epoxy resin, and the remainder is a combination of any number of bisphenol A, bisphenol F, bisphenol S or hydrogenated bisphenol A epoxy resin.

[0017] In the above scheme, by introducing a certain amount of aliphatic epoxy resin, the chain softness of the epoxy resin coating can be improved, the local agglomeration phenomenon produced during the curing process can be reduced, and the uniformity of the curing of the entire coating can be improved. In the curing process, the molecular chains can move more freely, thereby improving the fluidity of the epoxy resin molecules when not fully cured. After fully cured, if too much linear aliphatic epoxy resin is added, since the rigidity of the aliphatic epoxy resin itself after curing is not as good as that of the epoxy resin with aromatic groups, it will have an adverse effect on the wear resistance and smoothness of the surface.

[0018] In addition, on the basis of the above, in component A or component B, no more than 5 parts by weight of auxiliary agents may be included, and the auxiliary agents may be any number of anti-ultraviolet agents, antioxidants, and ion inhibitors. By adding corresponding components, the heat resistance, ultraviolet resistance, oxidation resistance and other properties of the system can be improved.

[0019] In addition, the present application also provides a method for preparing the above-mentioned UV-curable water-based insulating coating, comprising the following steps: mixing component A and component B, rapidly applying the mixture to the surface to be coated, and then heating and curing the mixture.

[0020] In summary, the present application provides a UV-curable water-based insulating coating with high flatness and high wear resistance, which can be used on the surface of automotive batteries, has good flatness, and is not easily damaged by friction during repeated use, thereby improving durability and safety performance. DETAILED DESCRIPTION

[0021] The technical solution of the present application is further described through the following specific implementation methods.

[0022] In the present application, the specific surface area of ​​the inorganic filler is measured by BET.

[0023] The performance of the coating is characterized by the following methods: The friction coefficient of the epoxy resin coating after curing was measured using a friction coefficient tester The wear quality of the epoxy resin surface was measured by a sandblasting impact tester.

[0024] Other properties: Refer to HG T4759-2014 to determine whether the adhesion grade, water resistance, acid resistance, alkali resistance, moisture and heat resistance, salt spray resistance, surface drying time and actual drying time of stainless steel, aluminum and PET meet the indicators. Among them, the grading test of adhesion is carried out in accordance with ISO 2409:2007.

[0025] Preparation example: This part mainly studies the preparation of three types of silica systems using non-modified, aminosilane coupling agent modified and long-chain amino modified as the first filler, and selects silica particles of different particle sizes. Among them, the caprolactam method for silica particles can refer to the literature "Preparation of Nano-SiO2 Surface Initiated Grafted PA6" (Liu Xi et al., College of Chemistry and Chemical Engineering, Hunan University, published in "Synthetic Resins and Plastics" 2010 Issue 27), and the silane coupling agent modification of silica is obtained by dissolving silica in a mixed solution of ethanol and water and reacting with HK550.

[0026] In the following examples, the amino-functionalized (or non-functionalized control) silica particles used are numbered as shown in Table 1.

[0027] Table 1 It should be noted that in the above table, the mass of the silane coupling agent is calculated by the amount added, and the mass of the caprolactam grafted is calculated by the mass increase of the silica particles after the reaction.

[0028] Example 1: In this example, the ratio of each component is fixed, and different silica in the preparation example is used as the first filler. Specifically, the ratio of each component is as follows: Component A: 100 parts of water-based epoxy resin, including 90 parts of hydrogenated bisphenol A epoxy resin (epoxy value 0.18), 10 parts of aliphatic epoxy resin (aliphatic cyclopentane resin 2021P is selected); 10 parts of non-ionic emulsifier, Tween 60 is selected; 10 parts of diluent, ethyl acetate is selected; 5 parts of the second filler; 0.5 parts of polyacrylic acid leveling agent, BASF Efka FL 3755; 3 parts of dimethyl silicone oil, 3000cs viscosity; The amount of water should not exceed 5 parts, and should be added in appropriate amount depending on the overall fluidity.

[0029] Component B: 10 parts of polyamide curing agent, amine value 8500mgKOH / g; 5 parts of the second filler, nano-alumina, with an average particle size of 140nm and a thermal conductivity of 4.5W / m·K; 1 part of gas silicon 5-10 parts of water, add appropriate amount depending on the overall fluidity.

[0030] In Example 1, the effects of different first fillers on coating properties are shown in Table 2.

[0031] Table 2 In the above experiment, it can be seen that three types of first fillers are used in this application. In the overall flatness trend, it can be clearly seen that the surface smoothness and wear resistance of the polycaprolactam grafted silica are significantly higher than those of the silica modified by the amino-containing silane coupling agent, and are better than the unmodified silica. This proves that the introduction of a certain polyamide structure into the surface through the polymer can effectively improve the step-by-step uniformity between the overall polymer and the filler, and thus the surface flatness. At the same time, the reaction sites on the surface of silica are used to participate in the reaction of the epoxy resin, and the longer molecular chains provide multiple reaction sites and a softer reaction structure, so that the silica can play a role in enhancing the strength of the epoxy resin, thereby improving the wear resistance.

[0032] For the overall particle size of the first filler, on non-modified silica, the smaller the overall particle size, the lower the friction coefficient. However, for amino-functionalized silica, whether it is functionalized by a silane coupling agent or by polycaprolactam, it has an optimal molecular weight distribution of 1 to 10 μm. The reason may be that too small a particle size will result in the first filler surface participating in the reaction with only a few sites, thereby reducing the activity of the reaction and affecting the amino groups on the silica surface from playing their role.

[0033] In addition, for the grafting mass of polycaprolactam, overall, the grafting mass has a better effect in the range of 100-500% of the mass of silica. Although further increasing the grafting mass of polycaprolactam has little effect on the surface roughness, it will significantly reduce the wear resistance of the system.

[0034] Example 2: Based on Examples 1-16, the amounts of the first filler in component B and the second filler in component A are further adjusted. The experimental results are shown in Table 3.

[0035] Table 3 In the above experiment, it can be seen that only when the first filler is in the range of 1-5 parts by mass and the second filler is in the range of 5-8 parts by mass, the system can better balance adhesion, friction coefficient and wear resistance. Even when the total amount is close, too much second filler and too little first filler will lead to an increase in friction coefficient and poor wear resistance, while too much first filler and too little second filler will lead to a longer surface drying time and actual drying time of the system, weaker reaction performance, and also cause a decrease in adhesion.

[0036] Example 3, based on Examples 1-16, the amounts of gas silicone, silicone oil, diluent and polyacrylic leveling agent in component A, as well as the selection of silicone oil viscosity are adjusted, as shown in Table 4.

[0037] Table 4 Experiments were conducted on the groups in Table 4, and the results are shown in Table 5.

[0038] Table 5 From the data in Table 5, it can be seen that adding polyacrylic leveling agent, silicone oil and gas silicon to the system to adjust the flow and leveling performance of the system can effectively adjust the overall fluidity to improve the surface smoothness of the system and have a significant effect on the friction coefficient of the surface. In addition, the amount of gas silicon should not be too much. Although increasing the amount of gas silicon has a better effect on the smoothness and wear resistance of the system, its excessive increase will lead to a significant increase in the surface drying time and actual drying time of the system, and when the gas silicon increases to more than 2 parts by mass, it will have an adverse effect on the flatness of the system.

[0039] Silicone oil can adjust the viscosity and improve the surface wear resistance in the system, and the viscosity of the silicone oil needs to be controlled at 1000-5000cs.

[0040] Example 4, based on Examples 1-16, the second filler used was adjusted. Specifically, different second fillers were selected, and their parameters such as type, specific surface area and average particle size are shown in Table 6.

[0041] Table 6 The parameter results of selecting different second fillers are shown in Table 7.

[0042] Table 7 The above experiments show that aluminum oxide, silicon nitride and zinc oxide all have good thermal conductivity coefficients, but the surface smoothness and wear resistance of aluminum oxide and silicon nitride as the second filler are significantly better than the epoxy coating when zinc oxide is used as the second filler. As for calcium carbonate particles, although their surface smoothness is good, their thermal conductivity is very poor, their application in batteries is very limited, and their wear resistance is also poor.

[0043] Example 5. In this example, the proportion of aliphatic epoxy resin in water-based epoxy resin is adjusted, the total mass of water-based epoxy resin is controlled to remain unchanged, and experiments are carried out. The experimental results are shown in Table 8.

[0044] Table 8 From the above experimental results, it can be seen that adding a small amount of aliphatic epoxy resin can improve the fluidity of the epoxy resin, and thus have better surface smoothness than pure aromatic ring epoxy resin. However, the amount added should not be too much, otherwise it will affect the adhesion and wear resistance of the system at the same time.

[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A UV-curable water-based insulating coating, characterized in that: It comprises component A and component B, wherein component A comprises the following components in parts by mass: Water-based epoxy resin 100 parts Nonionic emulsifier 5-20 parts 5-10 parts of diluent 5-8 parts of the second filler Polyacrylic acid leveling agent 0.1~1 part 2-4 parts silicone oil 0.5~2 parts of gas silicon 0-5 parts water Component B includes the following components in parts by mass: Curing agent 8-15 parts 1~5 parts of the first filler 5-10 parts water The curing agent is a polyamide compound, and the amine value of the polyamide compound is 5000 to 10000 (mgKOH / g); The first filler is amino-functionalized silica; The viscosity of the silicone oil is 1000-5000 cs.

2. The UV-curable water-based insulating coating according to claim 1, characterized in that: The average particle size of the amino-functionalized silica is 1 to 10 μm.

3. The UV-curable water-based insulating coating according to claim 1, characterized in that: The amino-functionalized silica is silica grafted with polycaprolactam.

4. The UV-curable water-based insulating coating according to claim 3, characterized in that: The mass ratio of the polycaprolactam to the silicon dioxide is 1 to 5:

1.

5. The UV-curable water-based insulating coating according to claim 1, characterized in that: The number average molecular weight of the curing agent is 3000-5000.

6. The UV-curable water-based insulating coating according to claim 1, characterized in that: The thermal conductivity of the second filler is not less than 2.5 W / m·K, and the average particle size of the second filler is not greater than 1 μm.

7. The UV-curable water-based insulating coating according to claim 6, characterized in that: The second filler is nano-aluminum oxide or nano-silicon nitride, and the average particle size is 50-200nm.

8. The UV-curable water-based insulating coating according to claim 1, characterized in that: The waterborne epoxy resin contains an aliphatic epoxy resin accounting for 5-10% by mass of the epoxy resin, and the remainder is a combination of any number of bisphenol A, bisphenol F, bisphenol S or hydrogenated bisphenol A type epoxy resin.

9. The UV-curable water-based insulating coating according to claim 1, characterized in that: Component A or component B further comprises an auxiliary agent in an amount of not more than 5 parts by weight, wherein the auxiliary agent is any number of an anti-ultraviolet agent, an antioxidant, and an ion inhibitor.

10. The method for preparing the UV-curable water-based insulating coating according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing component A and component B, rapidly coating the mixture on a plane to be coated, and then heating and curing the mixture.

Citation Information

Patent Citations

  • Light high-strength automobile side door plate and preparation method thereof

    CN108690326A

  • Insulating coating with high temperature resistance

    CN108949015A

  • Wear-resistant anticorrosive paint for polar ships and preparation method thereof

    CN110903734A

  • SiO2 grafted polyamide curing agent toughened and modified epoxy resin and preparation method thereof

    CN111393802A

  • Waterborne epoxy resin insulating paint and preparation method thereof

    CN116285584A